Academic Self-esteem as a Buffer Between Negative Youth Experiences and Academic Achievement in African American Adolescents. Issue 5 (July 2023) - Hodge, Jarrad D.; Cunningham, Michael
The study examines if African American adolescents' academic self-esteem moderates relations between negative youth experiences and academic achievement. Grounded in a PVEST perspective, the study collected responses from 364 Black adolescents (69% girls) in a southern, urban city. The primary finding in the study confirmed the hypothesis that students who report more negative youth experiences would also report lesser achievement and that negative relations would be buffered by the presence of Academic Self-Esteem. The study also outlines sex differences as Black males appear to be more vulnerable to negative youth experiences. Despite reporting more encounters with neighborhood-based discrimination, Black males appear to benefit academically when negative experiences are coupled with high academic self-esteem. The highest achievement in our sample was reported by students with high academic self-esteem who also reported higher instances of negative youth experiences. Intervention efforts and suggestions for future directions are discussed.